Analisis Optimalisasi Kapasitas Sistem Ventilasi Exhaust Berdasarkan Jumlah Lemari Penyimpanan Cairan Volatil di Laboratorium Industri Pelumas - Elysia Callysta Wibowo; Firra Rosariawari (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2025)
This study analyzes the conditions of extreme overcapacity in an installed exhaust ventilation system (Qinstalled = 18.00 /minute) that serves four acid cabinet units, specifically for the storage of volatile Hazardous and Toxic Materials (B3) such as toluene and methanol in tightly sealed containers. Although high capacity ensures safety, this practice causes significant energy inefficiency and unnecessary negative pressure problems in the room. Based on engineering analysis using a conservative Air Change Rate (ACR) standard of for liquid storage of 1.38 /minute. By applying the industry standard safety factor (FoS) of 1.5, the ideal flow rate (Qideal) that must be allocated is 2.07 . The optimization analysis concludes that the currently installed system is theoretically capable of safely and efficiently serving 8 units of volatile storage acid cabinets, with the addition of 4 new cabinets to maximize efficiency and reduce energy waste. This utilizes 92% of the total capacity while maintaining a safety factor above 1.5.